Sulforaphane as a preventive agent in Oral Cancer- A Systematic Review - M. Parasakthi; Kavitha Sanjeev (Oral Oncology Reports)
Background: Cancer is one of the leading causes of death worldwide. Of these, oral cancer is the sixth most common malignancy. Several phytochemicals are emerging these days in prevention of oral cancer. Sulforaphane present in broccoli is one such agent to prevent it. Aim: Sulforaphane component possesses anti-cancer properties. The aim of this systematic review is to identify and analyse the efficacy of sulforaphane in prevention of oral cancer. Methods: A PubMed, Scopus and Google Scholar search was performed using the MeSH terms [Medical subject headings] Broccoli and oral cancer prevention, Sulforaphane and oral cancer prevention. The search yielded 340 articles totally without any time restrictions. Of these, only two articles that met the inclusion criteria were selected. The review was conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines 2020. Results: The findings of the studies by various analytical methods showed that sulforaphane can prevent oral cancer. Conclusion: Based on the analysis of studies included in this systematic review, sulforaphane is found to be effective in prevention of oral cancer. But further clinical trials are necessary to assess the effects of sulforaphane on oral cancer patients.